Enhanced alloresponse to platelet transfusion due to immune dysregulation following ablative chemotherapy in mice - Jackman, Rachael P.; Darst, Orsolya; Gaillard, Betty; Tran, Johnson Q.; Tomayko, Mary M.; Muench, Marcus O. (Frontiers in Immunology, 2023)
Alloimmunization is common following platelet transfusion and can result in negative outcomes for recipients such as refractoriness to subsequent transfusions and rejection of transplants. Healthy people do not receive blood transfusions, and the diseases and therapies that result in a need to transfuse have significant impacts on the immunological environment to which these alloantigens are introduced. Ablative chemotherapies are common among platelet recipients and have potent immunological effects. In this study, we modeled the impact of chemotherapy on the alloresponse to platelet transfusion. As chemotherapies are generally regarded as immunosuppressive, we hypothesized that that they would result in a diminished alloresponse. Mice were given a combination chemotherapeutic treatment of cytarabine and doxorubicin followed by transfusion of allogeneic platelets, and compared to controls given no treatment, chemotherapy alone, or transfusion alone. Alloantibody responses were measured 2 weeks after transfusion, and cellular responses and growth factors were monitored over time. Contrary to our hypothesis, we found that chemotherapy led to increased alloantibody responses to allogeneic platelet transfusion. This enhanced response was antigen-specific and was associated with increased CD4 + and CD8 + T cell responses. Chemotherapy led to rapid lymphocyte depletion followed by reconstitution, non-specific activation of transitional B cells with the highest levels of activation in the least mature subsets, and increased serum levels of B cell activating factor (BAFF). These data suggest that ablative chemotherapy can increase the risk of alloimmunization and, if confirmed clinically, that additional measures to protect these patient populations may be warranted.